Marine fishes exhibit exceptional variation in biofluorescent emission spectra - Emily M. Carr; Mason A. Thurman; Rene P. Martin; Tate S. Sparks; John S. Sparks (PLoS ONE, 2025)
Biofluorescence is a phylogenetically widespread phenomenon among marine fishes, yet the phenotypic diversity in fluorescent emission wavelengths (e.g., green, red) remains poorly studied across the broad diversity of marine teleosts. In this study we investigate the fluorescent emission spectra from a diverse array of 18 teleost families and record fluorescent emission peaks over multiple body regions. Our results show that fluorescent emission spectra are remarkably diverse among teleost families, as well as within genera. Fluorescent emissions also vary across different body regions within some individuals. We show that members of the families Gobiidae, Oxudercidae, and Bothidae exhibit at least six distinct, non-overlapping fluorescent emission peaks. Nine of the 18 families examined in this study were found to have at least four distinct and non-overlapping fluorescent emission peaks. Further, we find that several families exhibit multiple discrete emission peaks for a single fluorescent color (i.e., wavelength range), including multiple distinct peaks within the green and red portions of the spectrum. The interplay between different fluorescent emission wavelengths and notable variation in the distribution of fluorescence on the body could allow for a wide array of fluorescent patterns to be produced by an individual or among closely related species. Our results reveal far more diversity in both fluorescent emission wavelengths (colors) and in the distribution of fluorescent molecules across the body than had previously been reported in the literature. We characterize this novel variation in biofluorescent emissions across an array of teleost families and discuss the potential implications of this exceptional phenotypic variability.